Risk Factors for Work Accidents in Farmers in Karuni Village, Southwest Sumba Regency - Mardianto Krisantus Ngongo; Anderias Umbu Roga; Mustakim Sahdan (Lontar : Journal of Community Health, 2022)
A workplace accident is an accident in a working relationship as an unexpected and unexpected event that is a direct result of work or the work environment or an accident that occurs while the work is being carried out. Work accidents could be caused by age, workloads, fatigue, and personal protective equipment (PPE). This study aimed to analyze the relationship between age, workload, fatigue, and PPE use on work accidents among Karuni Village, Loura District, and Southwest Sumba Regency farmers. This research was analytical survey research with a cross-sectional design. Data was collected using interviews, observation, and measurement techniques for 78 paddy farmers by simple random sampling. Data analysis used the chi-square test. The results showed a significant relationship between age, workload, fatigue, and the incidence of work accidents in rice farmers where the p-value <0.05. Meanwhile, there was no relationship between PPE use and work accidents in rice farmers where the p-value was>0.05. Relevant agencies are expected to activate the Occupational Health and Safety program through socialization, promotion, and routine supervision of informal sector businesses, especially rice farmers